PENGARUH PERMEABILITAS TERHADAP STABILITAS KEAMANAN BENDUNGAN GUNUNGROWO - Afrizon Kamiruddin; Abdul Chalid; Agus Sulaeman; Chandra Afriade Siregar (Universitas Kristen Maranatha, 2022)
Gunungrowo Dam has been establishing in 1925, it is located on the Wadi River. This dam is a homogeneous earthfill dam with a height of 20.5 m, with a storage capacity of 5.11 million m3 to supply irrigation water for an area of 6,000 Ha. Because the operational period is approaching 100 years, it is necessary to evaluate the level of stability and safety of the dam. The purpose of this study was to 1) determine the stability of the seepage safety in various reservoir water levels; 2) determine the slope safety stability (Safety Factor) of the dam in various reservoir water level conditions; 3) determine the effect of the dam body core permeability variable on seepage, and 4) determine the effect of the dam body core permeability variable on slope stability. The main discussion in this study is to analyze the stability of the dam safety using the GeoStudio-2012 computer program with SEEP/W features on seepage discharge and SLOPE/W on SF (Safety Factor) slopes. The SEEP/W modeling uses the concept of saturated soil mechanics. The input parameters for slope stability analysis are dam dimensions, type of material, bulk density (γ), cohesion (c), and shear angle (j). The study was conducted on all seepage discharge values and all SF values at minimum water level, normal water level, flood water level and fast receding with calculations without earthquake loads. The results of the study obtained that the SF value, discharge value, stable against landslide hazards and piping hazards met the safety requirements. Furthermore, from the seepage discharge value and the SF value, it is studied how the influence of the dam core permeability variable on the piping hazard and the potential for landslide hazard. From the results of the analysis, it is concluded that the greater the value of the permeability, the greater the seepage discharge and the greater the value of the permeability, the smaller the value of the safety factor.